Estudo do conceito Povo de Deus na Lumen Gentium - Jordão, José Cláudio (2012)
The Dogmatic Constitution Lumen Gentium on the Church, elaborated in the Ecumenical Council Vatican II, recovers the concept "People of God" to qualify the group of the baptisms believers, be them, clergyman, religious, nuns or lay. It was promulgated by Pope Paulo VI on November 21, 1964, entering for the history of the Church. as a "divisor of waters" in the theological subjects in ecclesiastical. That study intends to deepen the understanding of that concept. In the itself text of the studied document, there is the acknowledgement: "was pleased, however, to God to sanctify and to save the men, no individually, excluding all the relationship among them, but forming actually with them a people, that knew him in the truth and served him in sanctity" (LG 09). Therefore, the concept People of God, it has biblical roots that are essential in its recital, though, this study is more turn over to the subjects ecclesiastical of the Council, the before, the during and the after, particularly in the Church of Latin America. The objective was to study the concept People of God starting from Lumen Gentium cooperating so that the understanding of that concept can be enlarged among the clergyman, religious persons and nons. It had as hypothesis to be proven that the concept People of God present in the Dogmatic Constitution on the Church from Conclílio Vatican II still is not understood completely in its significanse for many baptisms believers. That study has used of the deductive method with bibliographical researches. It has had also as theoretical references the Scriptures, the key document in the discussions of the theme; a Lumen Gentum, as well as, other documents of the Teachership, besides works and periodic articles about the subject. With the development of that study it was verified that it is not still clearly understood that concept, because the hypothesis that it is not still completely understood the true meaning from the concept People of God, for many baptisms believers it was confirmed